The The Role of Bank NTB Syariah in Supporting Capital in Red Onion Farming Businesses in Hidirasa Village, Wera District, Bima District - Ramadhan, Tauhid Rejeki; Agustina, Ahadiah; Hindayanti, Nur Fitri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The role of Bank NTB Syariah in supporting capital for shallot farming in Hidirasa Village, Wera District, Bima Regency. This research aims to determine the role of Bank NTB Syariah in supporting the capitalization of shallot farming businesses in Hidirasa Village, Wera District, Bima Regency and to determine Bank NTB Syariah's policy in supporting capitalization of shallot farming businesses in Hidirasa Village, Wera District, Bima Regency. The research method used is qualitative with a descriptive analysis approach. Data was obtained through interviews and literature study. The results of the research show that the role of Bank NTB Syariah in supporting capitalization of shallot farming businesses in Hidirasa Village, Wera District, Bima Regency, namely: The role of Bank NTB Syariah in supporting capitalization of shallot farming businesses, supporting factors and obstacles in the implementation of sharia financing, the impact of financing on productivity and welfare of farmers, Bank NTB Syariah policy in supporting capital for shallot farming businesses, implementation of financing programs and their impact on farmers, and obstacles to shallot farming businesses.